Investigating secondary school physics teachers competency in using inquiry-based learning in Kebbi state, Nigeria - Bako, Aliyu (Institute of Advanced Scientific Research, Inc., 2020)
Myriad challenges and opportunities facing 21st-century students require competent teachers who can polish the talent of the students using student-centred learning methods like inquiry-based learning (IBL) in their classroom instruction, especially in teaching science. The purpose of this descriptive study is to determine the teachers’ competency in using IBL to teach physics in Kebbi state’s secondary schools. 30 physics teachers were randomlyselected from 36 physics teachers’ of Argungu zone secondary schools in Kebbi state to participate in this study. They were given a set of questionnaires to assess their competency in teaching Physics using IBL. The areas assessed include knowledge of the subject matter, teachers’ questioning technique, and attitude to practical skills. The result indicated that all three competencies have a mean score of lower than 3.5 out of 5. This shows that Kebbi state Physics teachers’ have low competencein implementing IBL.The paper recommended among others for Kebbi state physics teachers to be trained in questioning technique through professional development programs.